Bacteriology of Wound - Clinical Utility of Gram Stain Microscopy and the Correlation with Culture - Ana Kaftandzieva; Zhaklina Cekovska; Igor Kaftandziev; Milena Petrovska; Nikola Panovski (My University, 2012)
Aim: To determine the most common bacteria isolated from wound specimens and to compare those culture results to Gram stain slides. Material and methods: A total of 1970 specimens from 1788 patients, treated in the University Clinics in Skopje during a one year period were examined by standard microbiology techniques (inoculation onto standard agar media and direct Gram-stained smears). Automatized Vitek system was used for identification of all anaerobes. Results: Out of a total of 1970 specimens, 1094 (55.5 %) were positive by culture. A total of 1462 strains were isolated: 753 Gram positive (Gram+), 661 Gram negative (Gram-) and 48 anaerobic bacteria. The number of specimens yielding one, two or more different strains was 788, 244 and 62, respectively. Gram + bacteria, in 44.7 % of positive samples were a single isolate. The most commonly isolated potential pathogen was Staphylococcus. In 23.7% samples, Gram negative bacteria were a single isolate (E. coli was the most common isolate). 1094 specimens were positive by culture, 419 (38.3%) were positive by both culture and Gram stain and 675 (61.7%) were negative by Gram stain (leukocytes were present in 276 specimens). 876 specimens were negative by culture, 789 (90%) were negative by both culture and Gram stain (leukocytes were present in 271 specimen) and 87 (9.9%) were positive only by Gram stain. Conclusion: Our study demonstrated only a 38.3 % of microbiological correlation between Gram stain and culture. This data makes the clinical utility of Gram stain for the microbiological analysis of wounds questionable.
Keywords: wound; Gram stain slide